THE AANALYSIS OF STUDENTS’ REASONING ABILITY IN PALEMBANG - Dewi, Safira Permata; Rustaman, Nuryani; Sriyati, Siti (Journal of Biology Education, 2017)
This study aims to get a picture of class VIII students' reasoning in an A accredited school in Palembang City through method of survey. A number (n = 151) of grade VIII students came from four schools. TIMSS Biology Problems used are a matter of reasoning type both in the form of multiple choice and constructive response. The results showed that the reasoning of the students of class VIII had a good performance and showed normal distribution. The achievement of students in solving the problem of multiple choice is better than the matter of constructive response. Students find it difficult to solve a demanding problem for designing an experiment. The results of this research can be used in order to train students to develop the skills of deployment and improvement of quality of Biology learning process in school.   Keyword: Reasoning, TIMSS 2011, Palembang City